Proposal of a framework for aligning innovation initiatives with a focus on consumers and core competencies - Gibbin, Randal Victor; Agostinho, Oswaldo Luiz; Campos, Carlos Roberto (Brazilian Journal of Production Engineering, 2021)
Context: Innovation in organizations is a topic that has been intensely discussed, however, the need to create a construct that verifies the effectiveness of innovation initiatives is identified, by analyzing their alignment with core competencies and the focus on consumer.Objective: This work aims to propose a framework that verifies the alignment of organizational innovation initiatives with their core competencies and focus on the consumer, such elements are part of the construction of competitive advantage, as proposed by Agostinho (1995, 2012, 2014).Method: The proposed framework was determined through bibliographical research and verified its validity and application in a single case study in an organization in the field of diagnostic medicine, using the Business Model Canvas and Value Proposition Canvas tools for mapping purposes. core competencies and consumer focus respectively, relating them to innovation initiatives.Results: The representation with the Business Model Canvas was effective in determining the organization's core competencies. The Value Proposition Canvas allowed an analytical view of the context of customer segments, enabling an analysis of the focus on the consumer. By applying the framework, it is possible to verify the alignment between the qualitative elements present in these two constructs and the innovation initiatives, in product and in process.Conclusion: The proposed framework was effective in verifying the alignment between the elements of core competencies, consumer focus and innovation, allowing a holistic view and evaluating the harmony between these elements.
Keywords: Innovation; core competencies; focus on consumer; canvas